Percutaneous Image-Guided Biopsy of the Spleen - Sabir, Sharjeel H.; Tam, Alda L. (Digestive Disease Interventions, 2018)
Percutaneous spleen biopsy has a small but important role in the diagnostic approach to splenic lesions. Nonetheless, there remain concerns about the safety of the procedure, limiting its use despite evidence that splenic biopsy performed with optimum technique has comparable diagnostic yield and safety as other solid organ biopsies. To assure appropriate use of percutaneous image-guided spleen biopsy, we discuss the rationale, technique, and outcomes of the procedure.
Keywords: spleen; biopsy; diagnosis